Understanding the electrocatalytic role of magnesium doped bismuth copper titanate (BCTO) in oxygen evolution reaction - Kumar Maurya S.; Soni A.; Malviya M.; Tiwary D. (My University, 2025)
Designing high-efficiency electrocatalysts for water oxidation has become increasingly important in the catalysis field owing to its implications for renewable energy production and storage. The production of hydrogen (H2) from water is hampered by the very sluggish kinetics of the water-splitting process. Enhancement of effective oxygen evolution reaction (OER) electrocatalysts is also required to understand the primary barrier to OER. This article investigates the electrochemical activity of magnesium-doped bismuth copper titanate (Mg-BCTO) as an efficient catalyst for the OER in water electrolysis, a critical step in hydrogen production for sustainable energy. The synthesized materials, including various stoichiometries of Mg-doped BCTO, undergo thorough physical and electrochemical characterization using XRD, FT-IR, Raman, SEM, TEM, XPS, CV, EIS, and Tafel polarization analyses. Remarkably, Mg0.1 doped BCTO demonstrates superior performance, achieving a current density of 10 mA cm−2 at a very low overpotential (η10) of 265 mV and with a Tafel slope of 92 mV dec−1. This finding not only highlights the electrocatalytic efficiency of Mg doped BCTO but also positions it as a promising model for the development of highly active and stable water oxidizing catalysts, contributing to the advancement of clean energy technologies. © 2024 Elsevier B.V.